Experimental study on creep failure characteristics of coal mass under multistage stress and construction of prediction model - Yang, Yiran; Li, Yanzhong; Yuan, Kekuo; Lu, Zidong; Li, Gang (Frontiers in Earth Science, 2023)
The creep and failure mode of stratified coal is complex and challenging to predict. This is highly attributed to the internal stratified structure generated during coal forming. In this study, the inner stratified structure of coal during creep failure was explored. The evolution relationship between the key creep parameters and the inner stratified structure was evaluated through creep tests. The creep failure characteristics of coal under complex stress were determined. A neural network model was established to predict the creep failure modes, and the output results were subjected to smoothing and tracking to reduce the error. The results showed distinct creep characteristics of coal with various types of stratified structure. Key parameters such as creep variable, steady creep state and creep rate exhibited a nonlinear relationship with stress. The dual control neural network model constructed in the study showed high accuracy and stability. This model can be used as a guidance and reference for the study of creep failure mechanism and elucidation of creep behavior prediction of stratified coal.